The ultraviolet continuum slopes (β) of galaxies at z ≃ 8-16 from JWST and ground-based near-infrared imaging. Issue 1 (10th January 2023) - Cullen, Fergus; McLure, R J; McLeod, D J; Dunlop, J S; Donnan, C T; Carnall, A C; Bowler, R A A; Begley, R; Hamadouche, M L; Stanton, T M
ABSTRACT: We study the rest-frame ultraviolet (UV) continuum slopes (β) of galaxies at redshifts 8 < z < 16 (〈 z 〉 = 10), using a combination of JWST ERO and ERS NIRCam imaging and ground-based near-infrared imaging of the COSMOS field. The combination of JWST and ground-based imaging provides a wide baseline in both redshift and absolute UV magnitude (−22.6 < M UV < −17.9), sufficient to allow a meaningful comparison to previous results at lower redshift. Using a power-law fitting technique, we find that our full sample (median M UV = −19.3 ± 1.3) returns an inverse-variance weighted mean value of 〈β〉 = −2.10 ± 0.05, with a corresponding median value of β = −2.29 ± 0.09. These values imply that the UV colours of galaxies at z > 8 are, on average, no bluer than the bluest galaxies in the local universe (e.g. NGC 1705; β = −2.46). We find evidence for a β − M UV relation, such that brighter UV galaxies display redder UV slopes ($\rm {d}β / \rm {d} M_{\rm UV} = -0.17 ± 0.05$ ). Comparing to results at lower redshift, we find that the slope of our β − M UV relation is consistent with the slope observed at z ≃ 5 and that, at a given M UV, our 8 < z < 16 galaxies are bluer than their z ≃ 5 counterparts, with an inverse-variance weighted mean offset of 〈Δβ〉 = −0.38 ± 0.09. We do not find strong evidence that any objects in our sample display ultra-blue UV continuum slopes (i.e. β ≲ −3) that would require their UV emission to be dominated by ultra-young, dust-free stellar populations with high Lyman-continuum escape fractions. Comparing our results to the predictions of theoretical galaxy formation models, we find that the galaxies in our sample are consistent with the young, metal-poor, and moderately dust-reddened galaxies expected at z > 8.